PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIA SMP NEGERI 35 PEKANBARU - Oci Kurniadi; Titi Solfitri; Maimunah Maimunah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is classroom action resesarch that aim to improve the mathematics learning outcomes with applied the learning cooperative model of Numbereds Heads Together (NHT)type. The research consist of two cycles, each cycles has four stages, which are planning, implementation, observation, and reflection. The subject of this research is students of class VIIA SMP Negeri 35 Pekanbaru in academic years 2018/2019, which amounted to 40 students consist of 16 boys and 24 girls. The instrument of data collection in this research were observation sheets and student mathematic test. The observation sheet were analyzed in qualitative descriptive, while the students mathematic test were analyzed in quantitative descriptive. The qualitative descriptive showed an improvement of learning process prior to the action on the first and second cycles. Most of students were very confidenced and activated in learning process, such as while there were finished mathematic’s problem that given, presenting the result of problems and giving the conclusion of learning. Number of students that reach Minimum Mastery Criteria increase from basic score to first test and second test. The results of this research showed an increasing number of student learning mathematics about knowledge of the basic score (42,5%) to the first test (52,5%) to the second test (57,5%). The result os this research show that applying cooperative learning model of Numbered Heads Together can improve mathematic learning outcomes from the students at class VIIA SMP Negeri 35 Pekanbaru in academic years 2018/2019 for the subject matter Social Aritmethic.Key Words: Mathematics learning outcomes, Cooperative learning, Numbered Heads Together(NHT), Classroom Action Research